Maran na moście. Sekretne konwersje Gustawa Herlinga-Grudzińskiego - Kołodziej, Dorota (Przestrzenie Teorii, 2023)
This article attempts to discuss conversion in Gustaw Herling-Grudziński’s stories. Characters in Grudziński’s pieces are neither Jews nor Catholics, they are – as Yirmiyahu Yovel writes in his book The other within – “hybrids, a composite entity in the middle”. The paper applies the figure of marranos from Yovel’s research to reinterpret conversion in Grudziński’s stories and biography and point out how this secret shapes inner conflict in his works.